Monthly Succession of Biofouling Communities and Corresponding Inter-Taxa Associations in the North- and South-West of the Arabian Gulf - Muthukrishnan, Thirumahal; Hassenrück, Christiane; Al Fahdi, Dhikra; Jose, Liny; Al Senafi, Fahad; Mahmoud, Huda; Abed, Raeid M. M. (Frontiers in Marine Science, 2022)
Marine biofouling is a complicated process involving changes within micro- and macro-fouling community, species co-occurrence, and inter-taxa association patterns. An investigation of all above-mentioned aspects has rarely been conducted so far. Our study aimed to compare the monthly succession of the biofouling community developed at two locations each in the north- (Kuwait) and south-west (Oman) of the Arabian Gulf (AG) over six months, and to explore the association patterns within microfouling and between micro- and macro-fouling communities on a temporal and spatial scale. Spatio-temporal effects on the abundance and composition of micro- and macro-fouling communities were detected based on total biomass, bacterial and phototroph abundances, macrofouling coverage and 16S rRNA gene sequencing. We documented the development of distinct ecological niches within the fouling community resulting in fundamentally different succession patterns depending on location. Network analysis revealed nine clusters of highly interconnected co-occurring fouling bacterial taxa (M1-M9), with strong association (both positive and negative) to microalgae and macrofoulers in both Kuwait and Oman. Early stages of Kuwait biofilm showed M7 (cyanobacterial OTUs) positively and negatively associated with the majority of diatoms and macroalgae (Cladophoraceae), respectively, unlike the later stages where M5 (composed of Vibrio spp.) was positively associated with polychaetes (Hydroides elegans). While the causal relationships behind the observed inter-taxa associations remain unknown, our study provided insights into the underlying dynamics of biofouling processes encountered in the north- and south-west of the AG. Comprehensive future investigations encompassing transcriptomic or metabolomic tools may be required to address the challenge of interpreting such complicated dynamics over time and space in a continuously changing environment.